2017
DOI: 10.1042/bcj20160849
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a multifunctional docking site on the catalytic unit of phosphodiesterase-4 (PDE4) that is utilised by multiple interaction partners

Abstract: Cyclic AMP (cAMP)-specific phosphodiesterase-4 (PDE4) enzymes underpin compartmentalised cAMP signalling by localising to distinct signalling complexes. PDE4 long isoforms can be phosphorylated by mitogen-activated protein kinase-activated protein kinase 2 (MK2), which attenuates activation of such enzymes through their phosphorylation by protein kinase A. Here we show that MK2 interacts directly with PDE4 long isoforms and define the sites of interaction. One is a unique site that locates within the regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…More recent studies revealed a loss of PDE4 regulation with advancing age (40). PDE4s are usually anchored to the correct location (e.g., the SER) by DISC1, but can become "unanchored" by MK2 inflammatory signaling (60,61), which may contribute to age-related loss of PDE4s from the dendritic compartment. Notably, inhibition of PDE4s can create an aged-like phenotype, reducing dlPFC neuronal firing (62) and increasing the production of pS214Tau in vitro (40).…”
Section: Aging Rhesus Monkeys: Unique Opportunity To Study the Etiolomentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies revealed a loss of PDE4 regulation with advancing age (40). PDE4s are usually anchored to the correct location (e.g., the SER) by DISC1, but can become "unanchored" by MK2 inflammatory signaling (60,61), which may contribute to age-related loss of PDE4s from the dendritic compartment. Notably, inhibition of PDE4s can create an aged-like phenotype, reducing dlPFC neuronal firing (62) and increasing the production of pS214Tau in vitro (40).…”
Section: Aging Rhesus Monkeys: Unique Opportunity To Study the Etiolomentioning
confidence: 99%
“…Calcium dysregulation may drive tau pathology in multiple ways, including activation of kinases that phosphorylate tau, and by inducing inflammatory processes that remove the brakes on tau phosphorylation. For example, high levels of calcium signaling may increase MK2 activity through activation of upstream kinases like p38 (77,78), which can inhibit and unanchor PDE4s (60,61) (Fig. 4).…”
Section: Aging Rhesus Monkeys: Unique Opportunity To Study the Etiolomentioning
confidence: 99%
“…Dynein activity is controlled by the multiprotein dynactin complex with which DISC1 associates (Kamiya et al 2005), and by the DISC1 binding partner LIS1 (Ozeki et al 2003;Brandon J Physiol 596.14 et al 2004) (Burdick et al 2008;Bradshaw et al 2009) and its accessory proteins NDE1 and NDEL1 (Cianfrocco et al 2015;Bradshaw & Hayashi, 2017). The DISC1 interactor and cAMP phosphodiesterase PDE4 also interacts with LIS1 Houslay et al 2017), NDE1 ) and NDEL1 (Collins et al 2008), and DISC1 and PDE4 control the composition of LIS1-NDE1-NDEL1 complexes via cAMP-dependent phosphorylation (Collins et al 2008;Bradshaw et al 2011;Murdoch et al 2011). It follows that DISC1 is likely to regulate retrograde cargo transport through interactions with LIS1, NDE1 and NDEL1 (Bradshaw et al 2011;Murdoch et al 2011), and that this mechanism may involve the second messenger cAMP, although the latter has yet to be proven.…”
Section: Neuronal Intracellular Traffickingmentioning
confidence: 99%
“…2D). The assumption that the proteins interacted directly was further verified using far-western techniques, in which immobilized GST-coupled versions of known PDE4A binding proteins UBC9 and P75 NTR (Houslay et al, 2017) and POPDC1 were overlaid with MBP-PDE4A4 ( Fig. 2E).…”
Section: Popdc1 Interacts Directly With Pde4mentioning
confidence: 85%